POFA : a potential partial cement replacement material in aerated concrete - Abdullah, K.; Hussin, M. W.; Zakaria, F.; Muhamad, R.; Abdul Hamid, Z. (2006)
The ever popular issue on environmental preservation and sustainability all over the world has lead to innovations of new material using by-products generated from various sectors resulting from never ending researches conducted. In Malaysia, Faculty of Civil Engineering of Universiti Teknologi Malaysia has been conducting researches for more than 14 years in attempt to utilize of palm oil fuel ash (POFA), a local by-product produced abundantly by palm oil mill. Recently attempts have been carried out to incorporate POFA to produce a new type of aerated concrete known as POFA aerated concrete. The objective of this investigation is to study the effects of increasing the levels of palm oil fuel ash (POFA) replacement towards the compressive strength of aerated concrete. Experiments have been conducted by replacing 10%, 20%, 30%, 40% and 50% of POFA by weight of Ordinary Portland Cement. All specimens were tested for the compressive strength at 28 days in accordance to BS1881: Part 116. Findings will be able to reveal the compressive strength performance in aerated concrete when incorporated with various level of POFA quantity as partial cement replacement in aerated concrete.